Magnetization measurement of single La0.67Ca0.33MnO3 nanotubes in perpendicular magnetic fields using a micromechanical torsional oscillator - Antonio, D.; Dolz, M.I.; Pastoriza, H. (Elsevier, 2010)
Fil: Antonio, D. Comisión Nacional de Energía Atómica; Argentina